Influence of whitening toothpaste on color, roughness, and microhardness of composite resins - Manis, Roberta Bueno [UNESP] (2017)
Aims: This study aimed to evaluate color stability (ΔE), surface roughness (Ra), and Knoop microhardness (KHN) of composite resins under simulated toothbrushing with whitening toothpastes and desensitizing toothpaste. Methodology: One hundred disks were made with composite resins: Filtek Z350 XT (3M/ESPE) and Grandio SO (VOCO) and divided into five subgroups: AS (Control I) - immersed in artificial saliva; CS (Control II) - immersed in coffee solution; LW - brushing with Colgate Luminous White; OD - brushing with Oral-B 3D White; and SP - brushing with Sensodyne Total Protection, as control. The LW, OD, and SP groups had the disks brushed daily with 120 cycles after immersion in coffee solution (10 min) for a period of 30 days. ΔE, Ra, and KHN were obtained at baseline and after the treatments. Data were analyzed by ANOVA and Tukey's tests (P < 0.05). Student's t- test and Bonferroni test were performed to compare variables. Results: ANOVA revealed significant differences for ΔE, Ra, and KHN. ΔE: the highest ΔE mean values for Filtek were presented by SP group. For Grandio, the highest values were presented by SP and CS. Ra: Both composite resins presented similar behavior, with the highest mean values for groups AS and CS. KHN: The groups OD and SP made the most alteration on the surface, reducing the KHN values. Conclusions: Whitening toothpaste and immersion in coffee influenced on color stability, surface roughness, and microhardness of composite resins.